2020
DOI: 10.1007/s00259-020-05093-2
|View full text |Cite
|
Sign up to set email alerts
|

Global and segmental absolute stress myocardial blood flow in prediction of cardiac events: [15O] water positron emission tomography study

Abstract: Purpose We evaluated the value of reduced global and segmental absolute stress myocardial blood flow (sMBF) quantified by [15O] water positron emission tomography (PET) for predicting cardiac events in patients with suspected obstructive coronary artery disease (CAD). Methods Global and segmental sMBF during adenosine stress were retrospectively quantified in 530 symptomatic patients who underwent [15O] water PET for evaluation of coronary stenosis detected by coronary computed tomography angiography. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…To our knowledge, only three studies have previously elaborated on the prognostic value of regional quantitative MBF parameters [25][26][27]:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, only three studies have previously elaborated on the prognostic value of regional quantitative MBF parameters [25][26][27]:…”
Section: Discussionmentioning
confidence: 99%
“…Both Harjulahti et al and Bom et al previously found quantitative regional flow parameters to confer prognostic value for the prediction of myocardial infarction and death [ 26 , 27 ]. However, several methodological differences must be noted between the present and both previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial perfusion imaging is a powerful noninvasive functional tool for risk stratification, recommended by clinical practice guidelines. [1][2][3][4][5] Compared with relative perfusion images, absolute quantification of myocardial blood flow (MBF) by positron emission tomography (PET) could improve risk stratification. 6 Global and regional perfusion provide information on different aspects of myocardial perfusion.…”
Section: Introductionmentioning
confidence: 99%
“…Myocardial perfusion imaging is a powerful non-invasive functional tool for risk strati cation, recommended by clinical practice guidelines (1)(2)(3)(4)(5). Compared with relative perfusion images, absolute quanti cation of myocardial blood ow (MBF) and myocardial ow reserve (MFR) by positron emission tomography (PET) could improve risk strati cation (6).…”
Section: Introductionmentioning
confidence: 99%